Random integral manifolds of systems of differential equations with unbounded operator in a Banach space - Kolomiyets, V. G.; Mel'nikov, A. I. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We establish existence conditions for a random integral manifold of a certain class of differential systems with unbounded sectorial operator and random right-hand side in a Banach space.